A loss‐of‐function mutation p.T256M in NDRG4 is implicated in the pathogenesis of pulmonary atresia with ventricular septal defect (PA/VSD) and tetralogy of Fallot (TOF). Issue 2 (9th January 2021) - Peng, Jiayu; Wang, Qingjie; Meng, Zhuo; Wang, Jian; Zhou, Yue; Zhou, Shuang; Song, Wenting; Chen, Sun; Chen, Alex F.; Sun, Kun
Abstract : Pulmonary atresia with ventricular septal defect (PA/VSD) is a rare congenital heart disease (CHD) characterized by a lack of luminal continuity and blood flow from either the right ventricle or the pulmonary artery, together with VSDs. The prevalence of PA/VSD is about 0.2% of live births and approximately 2% of CHDs. PA/VSD is similar to tetralogy of Fallot (TOF) in terms of structural and pathological characteristics. The pathogenesis of these two CHDs remains incompletely understood. It was previously reported that N‐myc downstream‐regulated gene (NDRG)4 is required for myocyte proliferation during early cardiac development. In the present study, we enrolled 80 unrelated patients with PA/VSD or TOF and identified a probably damaging variant p.T256M of NDRG4. The p.T256M variant impaired the proliferation ability of human cardiac myocytes (hCM). Furthermore, the p.T256M variant resulted in G1 and G2 arrest of hCM, followed by an increase in p27 and caspase‐9 expression. Our results provide evidence that the p.T256M variant in NDRG4 is a pathogenic variant associated with impaired hCM proliferation and cell‐cycle arrest and likely contributes towards the pathogenesis of PA/VSD and TOF. Abstract : N‐myc downstream‐regulated gene (NDRG)4 is widely expressed in human embryonic hearts. The p.T256M variant in NDRG4 resulted in G1 and G2 arrest of human cardiac myocytes, thereby impairing their proliferative ability, which likely contributes towards the pathogenesis of pulmonary atresia with ventricular septal defect and tetralogy of Fallot.